2018
DOI: 10.1007/s11250-018-1521-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices (KAP) related to brucellosis and factors affecting knowledge sharing on animal diseases: a cross-sectional survey in the dry zone of Sri Lanka

Abstract: Farmers' lack of knowledge is assumed to have affected the presence of brucellosis in Sri Lanka for decades. This study, carried out in the Ampara district in the dry zone of Sri Lanka, revealed that there is a significant knowledge gap for brucellosis compared to foot and mouth disease (FMD) (p < 0.001). Only 8.3% of farmers knew that brucellosis causes cattle abortions. Only 2.6% knew that it is zoonotic. The difference in knowledge of the symptoms and transmission of brucellosis and FMD was significant (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
11
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
7
11
3
Order By: Relevance
“…On the other hand, similar to previous reports from Ethiopia [ 13 , 14 ], Sri Lanka [ 27 ] and Nigeria [ 33 ]most of the study participants had no a clear information regarding the zoonotic importance and mode of transmission of the disease (as only 24 individuals mentioned that frequently consuming raw milk could cause hahayita), while they practice risk factors like touching aborted fetus, uterine discharge or retained placenta or aborted animals without protection and also consume raw milk from animals which have experienced abortion. This finding contrasts with the findings of studies from Uganda [ 18 ], Jordan [ 36 ] and Kenya [ 32 ] in which the majority of the respondents suggested consumption of unpasteurized dairy products as the main routes of infection in humans.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, similar to previous reports from Ethiopia [ 13 , 14 ], Sri Lanka [ 27 ] and Nigeria [ 33 ]most of the study participants had no a clear information regarding the zoonotic importance and mode of transmission of the disease (as only 24 individuals mentioned that frequently consuming raw milk could cause hahayita), while they practice risk factors like touching aborted fetus, uterine discharge or retained placenta or aborted animals without protection and also consume raw milk from animals which have experienced abortion. This finding contrasts with the findings of studies from Uganda [ 18 ], Jordan [ 36 ] and Kenya [ 32 ] in which the majority of the respondents suggested consumption of unpasteurized dairy products as the main routes of infection in humans.…”
Section: Discussionsupporting
confidence: 91%
“…Some of the study participants also raised the possibility that foot and mouth disease is another disease which causes abortion in their cattle. The pastoral community members’ concern about foot and mouth disease as a cause of abortion in their cattle is similar to the findings of a study by Kothalawala et al [ 27 ] in Sri Lanka where farmers identified this disease as a cause of abortion in their cattle, but they had no adequate information regarding brucellosis as a cause of abortion in animals. Evidence also shows that foot and mouth disease causes abortion in cattle [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this current study, although not statistically significant, the higher prevalence of OAB in high-risk regions correlates with previous findings reporting a high incidence of brucellosis in Middle Eastern countries such as Iran and Saudi Arabia [75,78,79]. Moreover, prevalence variation in different parts of the world may be due to varying environmental and socioeconomic factors such as sanitation, availability of medical facilities for optimum treatment and care, brucellosis awareness in communities, diagnostic capabilities for prompt detection of the disease condition, amongst others [80–83]. Another important factor is under-diagnosis or misdiagnosis of brucellosis because the disease manifests as flu-like symptoms and may bear resemblance to other diseases with similar symptoms such as malaria, or dengue fever, which are common disease conditions in many parts of Africa, thus leading to delays in detection and appropriate treatment of the disease [81,82].…”
Section: Discussionsupporting
confidence: 83%
“…Many factors are thought to be related to the level of awareness and knowledge of brucellosis. Several studies in the meta-analysis have indicated that education is positively associated with awareness and knowledge levels [28, 29, 39, 62, 80, 81, 92, 93, 95, 96]. It has been shown that previous experience with brucellosis in livestock and brucellosis prevalence levels are positively correlated with awareness and knowledge levels of brucellosis [107].…”
Section: Discussionmentioning
confidence: 99%